Effectiveness Extract Larvacides of Kecombrang Flower (Etlingera elatior) on Death of Aedes aegypti Mosquito Larvae - Anissa Permata Sari; Dian Saraswati; Annashr, Nissa Noor (CV. Get Press Indonesia, 2024)
The prevention and control of dengue hemorrhagic fever can be done by using natural larvicides whose content is safer, such as kecombrang plant (Etlingera elatior). Purpose: to analyze the effectiveness of extract larvacides of kecombrang flower with various concentrations on the mortality of Aedes aegypti larvae. Methods: this research used a pure experimental method (true experimental) with a post test with only one group design. The independent variable was kecombrang flower extract (Etlingera elatior) with concentrations of 0% (control), 2%, 4%, 6%, and 8% with 5 replications and an observation time of 6 hours. The dependent variable was the death of Aedes aegypti larvae. Data analysis consisted of descriptive and inferential analysis using the One-Way Anova test followed by the Post Hoc LSD (Least Significant Difference) test. Results and Discussion: the results of the research showed that there was a significant difference in mean mortality between various concentrations extract of kecombrang flower (p=0.000) and the most effective concentration was 6%. Results: There was a significant difference in mean mortality between various concentrations extract of kecombrang flower (p=0.000) and the most effective concentration was 6%. The result of probit test showed that the LC50 value was 6.577 and LC90 was 12.113 for 6 hours. Implications: The results of this study indicated that extract of kecombrang flower can help government efforts in controlling dengue fever and can be used by the community. Conclusion: kecombrang flower extract (Etlingera elatior) was effective in being used as a vegetable larvicide.